Modified salting‐out method: high‐yield, high‐quality genomic DNA extraction from whole blood using laundry detergent - Nasiri, H. (J Clin Lab Anal, 2005)
Different approaches have been used to extract DNA from whole blood. In most of these methods enzymes (such as proteinase K and RNAse A) or toxic organic solvents (such as phenol or guanidine isothiocyanate) are used. Since these enzymes are expensive, and most of the materials that are used routinely are toxic, it is desirable to apply an efficient DNA extraction procedure that does not require the use of such materials. In this study, genomic DNA was extracted by the salting‐out method, but instead of using an analytical‐grade enzyme and chemical detergents, as normally used for DNA isolation, a common laundry powder was used. Different concentrations of the powder were tested, and proteins were precipitated by NaCl‐saturated distilled water. Finally, DNA precipitation was performed with the use of 96% ethanol. From the results, we conclude that the optimum concentration of laundry powder for the highest yield and purity of isolated DNA is 30 mg/mL. The procedure was optimized, and a final protocol is suggested. Following the same protocol, DNA was extracted from 100 blood samples, and their amounts were found to be >50 µg/mL of whole blood. The integrity of the DNA fragments was confirmed by agarose gel electrophoresis. Furthermore, the extracted DNA was used as a template for PCR reaction. The results obtained from PCR showed that the final solutions of extracted DNA did not contain any inhibitory material for the enzyme used in the PCR reaction, and indicated that the isolated DNA was of good quality. These results show that this method is simple, fast, safe, and cost‐effective, and can be used in medical la‐ boratories and research centers. J. Clin. Lab. Anal. 19:229–232, 2005. © 2005 Wiley‐Liss, Inc.